Performance Analysis of Orbital Angular Momentum-Index Modulation 6G Waveform Short Field Communication - Sutanto, Yudi Sutanto; Teguh Yoga Putra (Jurnal PROCESSOR, 2024)
Currently, wireless communication is migrating from 5G to 6G. This is happening due to the new application of Sensory Transmission technology, Intelligent Transportation System (ITS), and Digital Twin. The problems that arise from the implementation of this migration are the band limits referred to in the regulations above, the reliable link range or the distance that communication is successful, and the increase in the number of users to be served. This study uses the performance results of Orbital Angular Momentum-Index Modulation (OAM-IM) compared to Orthogonal Frequency Division (OFDM) for short distance communication for each Bit Error Rate (BER) at the distances mentioned in the general description. The OAM-IM method can produce lower BER values than the OFDM method through descriptive statistical analysis, The simulation results are described in the form of tables and charts and compared to the lower BER of the two methods. The average BER of OFDM is 0.486818 while a lower BER is recorded in the OAM-IM method of 0.314013 for the proposed simulation.